Guided Inquiry Learning and Students' Achievement in Islamic Religious Education: A Correlational Study in an Indonesian Islamic Junior High School - Muhammad Naufal Farras; Iffah Mukhlisah; Sugiyat Sugiyat (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
Guided Inquiry Learning has been widely recognized as a learner-centered instructional approach that promotes active knowledge construction, critical thinking, and meaningful learning. However, empirical evidence regarding its relationship with students' academic achievement in Islamic Religious Education (IRE) remains limited, particularly within Indonesian Islamic junior high schools. This study aimed to examine the relationship between Guided Inquiry Learning and students' examination-based achievement in Islamic Religious Education. A quantitative correlational design was employed involving 43 seventh-grade students at SMP Muhammadiyah 2 Boyolali Program Khusus, Indonesia, selected using total sampling. Data on Guided Inquiry Learning were collected through a 25-item validated and reliable questionnaire, while students' academic achievement was measured using official Islamic Religious Education examination scores. The data were analyzed using descriptive statistics, assumption testing, Pearson correlation, and simple linear regression. The findings revealed that Guided Inquiry Learning was not significantly associated with students' examination-based achievement (? = 0.088; t = 0.568; p = 0.573), explaining only 0.8% of the variance in academic achievement (R² = 0.008). These findings suggest that examination scores may not fully capture the broader educational outcomes fostered by Guided Inquiry Learning, such as critical thinking, conceptual understanding, inquiry skills, and reflective learning. The study contributes to the growing literature by extending Guided Inquiry research to the context of Islamic Religious Education through a correlational approach using examination-based academic achievement as the primary outcome measure. Future studies are encouraged to incorporate broader indicators of learning outcomes and more comprehensive analytical models to better understand the educational contributions of Guided Inquiry Learning.